Current Trends and Impact of Liver Biopsy on Survival in Hepatocellular Carcinoma: A Korean Multicenter Analysis - Seong Joon Chun; Jeong-Ju Yoo; Sang Gyune Kim; Young-Seok Kim (Diagnostics)
Background/Objectives: The diagnosis of hepatocellular carcinoma (HCC) mainly relies on imaging, with biopsy reserved for cases where imaging results are inconclusive. While biopsy offers histological confirmation and can guide treatment decisions, its impact on survival outcomes in HCC patients remains uncertain. This study aimed to examine biopsy practices and evaluate their effects on survival rates in HCC patients. Methods: We analyzed data from 18,304 HCC patients in the Korean Primary Liver Cancer Registry from 2008 to 2019. We compared overall survival (OS) and transplant-free survival (TFS) between patients who underwent a biopsy and those diagnosed solely based on imaging. Results: From 2008 to 2019, liver biopsy rates varied, reaching a peak of 12.44% in 2009 and declining to 8.18% in 2012, with the majority of patients (90.3%) diagnosed through imaging. Trans-arterial chemoembolization was the most common treatment overall (40.5%), especially in the non-biopsy group. Sorafenib use increased significantly in both groups after 2015. Patients who underwent biopsy had lower OS (43.1 ± 1.29 months) and TFS (42.45 ± 1.28 months) compared to those diagnosed via imaging (OS: 54.5 ± 0.48 months, TFS: 52.57 ± 0.47 months, p < 0.001 for both). However, Cox regression analysis indicated that biopsy was not a significant risk factor for OS (HR: 1.021, p = 0.502) or TFS (HR: 1.013, p = 0.674). Subgroup analysis suggested that biopsy may benefit patients with advanced stage IV-B by enabling more aggressive treatment strategies. Conclusions: Liver biopsy rates fluctuated over time, with the majority of HCC diagnoses made through imaging. Although biopsy does not significantly affect OS or TFS, it may provide advantages in advanced cases, such as stage IV-B, by guiding more aggressive treatment strategies.